2012
DOI: 10.1097/ico.0b013e31823f0a64
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topical Human Amniotic Fluid and Human Serum in a Mouse Model of Keratoconjunctivitis Sicca

Abstract: HAF was superior to HS and artificial tears for improving corneal staining within 2 weeks of therapy in this induced mouse model of keratoconjunctivitis sicca. Clinical studies are needed to ascertain the benefits of these therapies in patients with ocular surface disorders associated with dry eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…One to 2 µL of the liquid was administered to the cornea by micropipette, and the residual liquids around the eye were washed by saline and wiped by filter paper gently. After fluorescein staining of the eye, the cornea was examined for corneal epithelial disorders using a slit-lamp microscope with a blue filter; these disorders were evaluated using a modified, previously described method [39]. In brief, corneal epithelial disorders were scored on a scale of 0–3 as follows: 0, no punctate staining (normal); 1, sparse punctate staining; 2, intermediate staining between 1 and 3; and 3, dense punctate staining.…”
Section: Methodsmentioning
confidence: 99%
“…One to 2 µL of the liquid was administered to the cornea by micropipette, and the residual liquids around the eye were washed by saline and wiped by filter paper gently. After fluorescein staining of the eye, the cornea was examined for corneal epithelial disorders using a slit-lamp microscope with a blue filter; these disorders were evaluated using a modified, previously described method [39]. In brief, corneal epithelial disorders were scored on a scale of 0–3 as follows: 0, no punctate staining (normal); 1, sparse punctate staining; 2, intermediate staining between 1 and 3; and 3, dense punctate staining.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies using animal models have demonstrated that pAF can benefit dry eyes, alkali burns, wound healing, and healing after excimer ablation. [9][10][11][12][13] In humans, AF has been used for severe dry eye and healing after chemical burns; however, it was not compared with other treatments in a controlled fashion. 14,15 In addition, there is an ongoing FDA clinical trial investigating pAF as a treatment of ocular chronic graft-versus-host disease.…”
mentioning
confidence: 99%
“…Several experiments have shown that AS eye drops suppress apoptosis in the ocular surface epithelium and increase goblet cell density in dry eye; the causal effect of albumin, the major protein in serum, has been suggested. In animal and in vitro studies of dry eye, albumin improved cellular damage and suppressed apoptosis in the ocular surface epithelium [29][30][31] . The aim of this study was to assess the level of apoptosis in conjunctival epithelial cells in patients suffering from severe DED before and after a three-month treatment with 20% AS-eye drops.…”
Section: Introductionmentioning
confidence: 99%